A importância da tutela responsável para o bem-estar do animal de estimação - Nascimento, Ana Paula da Silva (2023)
The research reported on the importance of responsible guardianship for the well-being of the pet. The guardianship responsible for a pet depends of the guardian's to want to keep it. Some tutors, when they wish not more to assume responsible guardianship, generally commit the following behaviors: donate the pet to other people, return it to the shelter, if the species was adopted in one of these places, or forwent it in the environment. To be a tutor is to have responsibility for the life of a vulnerable living being, which depends on that one to survive. The objectives of this research were: (1) to promote information about the precepts of responsible guardianship for pets, demonstrating that when it is practiced by the guardian, it can serve as a guarantee of protection against the abandonment of those in the environment. In beyond that, (2) it was also explained what would be responsible guardianship for a pet. Next, (3) it was explained how fundamental the role of the guardian is in relation to the responsibility for a pet, and finally, (4) solutions were proposed to be able to contribute to the reduction of abandonment of pets in the environment. The methodology of this research used several bibliographical references of books, articles, law, jurisprudence, etc. It was concluded in this research that the abandonment of pets in the environment it is because to the lack of commitment of the tutor in wanting to take responsibility for taking care of the adopted species until the end of its life. A specific law for the protection of pets is necessary, because the legislation still has gaps, and while as there is this legislative failure, these pets beings will continue depending of the your tutor to practice of the responsible guardianship.